IMPORTANCE OF CLASSICAL MORPHOLOGY IN THE DIAGNOSIS OF MYELODYSPLASTIC SYNDROME - Rosangela Invernizzi; Federica Quaglia; Matteo Giovanni Della Porta (Mediterranean Journal of Hematology and Infectious Diseases, 2015)
Myelodysplastic syndromes (MDS) are hematopoietic stem cell disorders characterized by dysplastic, ineffective, clonal and neoplastic hematopoiesis. MDS represent a complex hematological problem: differences in disease presentation, progression and outcome  have necessitated the use of classification systems to improve diagnosis, prognostication and treatment selection. However, since a single biological or genetic reliable diagnostic marker has not yet been discovered for MDS, quantitative and qualitative dysplastic morphological alterations of bone marrow precursors and of peripheral blood cells are still fundamental for diagnostic classification. In this paper World Health Organization (WHO) classification refinements and current minimal diagnostic criteria proposed by expert panels are highlighted and related problematic issues are discussed. The recommendations should facilitate diagnostic and prognostic evaluations in MDS and selection of patients for new effective targeted therapies. Although in the future morphology should be supplemented with new molecular techniques, the morphological approach, at least for the moment, is still the cornerstone for the diagnosis and classification of these disorders.